Smart Chicken Coop Control and Monitoring System Design Automatically with Smartphone Notifications - Sri Novida Sari; Romulo Aritonang; Sumarlin (ITScience (Information Technology and Science), 2021)
Technological developments and industrial automation encourage humans to meet their needs quickly. So that robotics technology was developed to help ease human work in the future. The chicken breeder is a business that has great profit prospects because the consumption of chicken meat in the community increases every year. It takes good management of chicken farmers so that farmers can get good harvests. In this study, the author designed a monitoring system to monitor conditions in the chicken coop such as temperature, light, feeding, and drinking. The smart chicken coop system that the author designed uses Smartphone notifications so that the condition of the chicken coop can be viewed and controlled using a smartphone via the internet/wifi network.